Changes in Lysine Methylation Contribute to the Cytotoxicity of Curcumin in Colon Cancer Cells - Roberta Santarelli; Paola Currà; Michele Di Crosta; Roberta Gonnella; Maria Saveria Gilardini Montani; Mara Cirone (Molecules)
Epigenetic abnormalities play a critical role in colon carcinogenesis, making them a promising target for therapeutic interventions. In this study, we demonstrated that curcumin reduces colon cancer cell survival and that a decrease in lysine methylation was involved in such an effect. This correlated with the downregulation of methyltransferases EZH2, MLL1, and G9a, in both wild-type p53 (wtp53) HCT116 cells and mutant p53 (mutp53) SW480 cells, as well as SET7/9 specifically in wtp53 HCT116 cells. The effects induced by curcumin were more pronounced in wtp53 cells, where it induced a stronger apoptosis and ferroptosis. Interestingly, curcumin also reduced mutp53 expression, suggesting that it could enhance the efficacy of other therapies, particularly in overcoming drug resistance mechanisms associated with mutp53. For instance, in this study, we show that curcumin sensitized SW480 cells to SET7/9 inhibition by sinefungin, further supporting its potential as a combinatorial therapeutic agent. However, although to a lesser extent, curcumin also impaired cell survival in HCT 116 p53 null cells, suggesting that other molecular pathways or factors, beyond p53, may be involved in curcumin-induced cytotoxicity.